Effects of silage from different maize varieties on growth traits, meat quality, slaughter performance, apparent digestibility of nutrients, and rumen microbiota in Hu sheep - Yan, Longfei; Hua, Jinling; Lu, Wenwen; Zhao, Huwei; Chao, Chen; Yan, Liang; Lv, Xiaokang (Frontiers in Animal Science, 2025)
In this study, we examined the impact of various maize to maize varieties on the performance and digestibility of hu sheep. A total of thirty-six healthy male hu sheep, all of similar weight, were selected and randomly assigned to one of three groups, each comprising 12 sheep. The groups were designated as CS1 (fed HanDan 777), CS2 (fed DengHai 605), and CS3 (fed NongDa 367). The study included a pre-feeding period of 10 days followed by an experimental period of 80 days. The findings indicated that the total weight gain and average daily gain in the CS2 group were higher than those in the CS1 group (p < 0.05), and the feed-to-weight ratio in the CS2 group was lower than those in the CS1 and CS3 groups (p < 0.05). The pre-slaughter live weight in the CS2 group was higher than in the CS1 and CS3 groups. Additionally, the L* value of the CS3 group was higher than those of the CS1 and CS2 groups (p < 0.05). The shear force of the CS3 group was greater than that of the CS2 group (p < 0.05). Compared with the CS1 group, both the CS2 and CS3 groups exhibited higher water loss rates (p < 0.05). Moreover, the cooking loss of the CS2 group was higher than those of the CS1 and CS3 groups (p < 0.05). There was a significant effect of the total weight gain and average daily weight gain in the CS2 group compared to the CS1 group (p < 0.05). These findings suggest that the DengHai 605 corn variety (CS2) is a suitable option for use as silage in Hu sheep diets due to its positive impact on growth performance.